The Control of Non Isothermal CSTR Using Different Controller Strategies - F. Zuhwar, Zahra’a (Iraqi Journal of Chemical and Petroleum Engineering, 2012)
In all process industries, the process variables like flow, pressure, level, concentration and temperature are the main parameters that need to be controlled in both set point and load changes. A control system of propylene glycol production in a non isothermal (CSTR) was developed in this work where the dynamic and control system based on basic mass and energy balance were carried out. Inlet concentration and temperature are the two disturbances, while the inlet volumetric flow rate and the coolant temperature are the two manipulations. The objective is to maintain constant temperature and concentration within the CSTR. A dynamic model for non isothermal CSTR is described by a first order plus dead time (FOPDT). The conventional PI and PID control were studied and the tuning of control parameters was found by Ziegler-Nichols reaction curve tuning method to find the best values of proportional gain (Kc), integral time ( I) and derivative time ( D). The conventional controller tuning is compared with IMC techniques in this work and it was found that the Ziegler –Nichols controller provides the best control for the disturbance and the worst for the set-point change, while the IMC controller results show satisfactory set-point responses but sluggish disturbance responses because the approximate FOPTD model has relatively small time delay. Feedforward and feedforward combined with feedback control systems were used as another strategy to compare with above strategies. Feedforward control provides a better response to disturbance rejection than feedback control with a steady state deviation (offset). Thus, a combined feedforward-feedback control system is preferred in practice where feedforward control is used to reduce the effects of measurable disturbances, while feedback trim compensates for inaccuracies in the process model, measurement error, and unmeasured disturbances. Also the deviation (offset) in feedforward control was eliminated.